Accounting calculations problems with suppliers and contractors - Tikholaz I. A. (Interactive science, 2016)
in the article an order of accounting reflection of payments with suppliers and contractors are researched and ways of enhancement of accounting calculations process development with the purpose of management decisions optimization for their implementation are offered. Theoretical bases of intraeconomic control of settlings with suppliers and contractors are developed.
Keywords: контроль; учет; расчеты; поставщики; accounting; control; источники информации; calculations; suppliers; подрядчики; contractors; sources of information